KONTRIBUSI KONSEP DIRI FISIK DAN MOTIVASI BERPRESTASI TERHADAP PERENCANAAN KARIER SISWA KELAS XI SMKN SE-KOTA PEKANBARU - Raja Arlizon; Zulfan Saam; Donal Donal (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2018)
The general objective of this research is to describe: (a) Level of physical self-concept boys and girls (b) The level of student achievement motivation of men and women,(c) Career planning level boys and girls, (d) Differences in physical self-concept, achievement motivation and career planning boy with girls, (e) Contribution of physical self-concept and achievement motivation to get her to career planning undertaken in-class XI SMKN Se-Kota Pekanbaru. This study uses a quantitative approach with correlation and comparative methods by making a proportional random sampling technique. In this study the following conclusions can be adduced: (a) Physical self-concept level boys and girls, in general, are in the medium category, (b) The level of student achievement motivation of men and women, in general, are in the category of being, (c) Level career planning toward boys and girls in general are at a high category, (d) There are differences in physical self-concept of boys and girls, (e) There were no differences in achievement motivation and career planning boys and the women, (f) There contribution of physical self-concept and achievement motivation on student career planning direction.